Glucose sensing by carotid body glomus cells: potential implications in disease - Gao, Lin; Ortega-Sáenz, Patricia; García-Fernández, María; González-Rodríguez, Patricia; Caballero-Eraso, Candela; López-Barneo, José (Frontiers in Physiology, 2014)
The carotid body (CB) is a key chemoreceptor organ in which glomus cells sense changes in blood O2, CO2, and pH levels. CB glomus cells have also been found to detect hypoglycemia in both non-primate mammals and humans. O2 and low-glucose responses share a common final pathway involving membrane depolarization, extracellular calcium influx, increase in cytosolic calcium concentration, and neurotransmitter secretion, which stimulates afferent sensory fibers to evoke sympathoadrenal activation. On the other hand, hypoxia and low glucose induce separate signal transduction pathways. Unlike O2 sensing, the response of the CB to low glucose is not altered by rotenone, with the low glucose-activated background cationic current unaffected by hypoxia. Responses of the CB to hypoglycemia and hypoxia can be potentiated by each other. The counter-regulatory response to hypoglycemia by the CB is essential for the brain, an organ that is particularly sensitive to low glucose. CB glucose sensing could be altered in diabetic patients, particularly those under insulin treatment, as well as in other medical conditions such as sleep apnea or obstructive pulmonary diseases, where chronic hypoxemia presents with plastic modifications in CB structure and function. The current review will focus on the following main aspects: 1) the CB as a low glucose sensor in both in vitro and in vivo models; 2) molecular and ionic mechanisms of low glucose sensing by glomus cells, 3) the interplay between low glucose and O2 sensing in CB, and 4) the role of CB low glucose sensing in the pathophysiology of cardiorespiratory and metabolic diseases, and how this may serve as a potential therapeutic target.